Influence of different irrigation solutions on the push-out bond strength of fiber posts to root dentin and root canal dentin microhardness: Methodological study - Erdem Hepşenoğlu, Yelda; Erşahan, Şeyda; Yılmaz, Burcu; Aydınoğlu, Aysu; Sağır, Kadir; Hazar Yoruç, Afife Binnaz (Turkiye Klinikleri, 2023)
Objective: This study aimed to compare the effect of sodium hypochlorite (NaOCl), chlorhexidine (CHX), ethylene diamine tetra acetic acid (EDTA) and etidronic acid (HEBP) solutions and their combinations on a push-out bond strength of fiber posts to root canal dentin and on root dentin microhardness. Material and Methods: Sixty human maxillary central incisors were sectioned below the cementoenamel junction, the roots were endodontically treated and were divided into 6 groups (n=10) according to the final irrigation protocol: (1) Distilled water, (2) CHX, (3) HEBP-NaOCl combination, (4) HEBP, (5) 2.5 % NaOCl, (6) 17% EDTA. The fiber posts were then cemented with self-etching resin cement. Bonded specimens were cut (1-mm-thick), the first slice of the coronal 3rd was used for dentin microhardness analysis, and other slices were used for the push-out bond strength test. The data were statistically analyzed by using Shapiro-Wilk, Oneway ANOVA, and the Games-Howell test. Results: The lowest microhardness was observed in HEBP-NaOCl and NaOCl (p<0.05). CHX, HEBP, and EDTA resulted in less reduction in microhardness as compared to other groups (p<0.05). HEBP-NaOCl and NaOCl showed significantly higher mean bond strength to root dentin in the cervical thirds than in other groups (p<0.05). Conclusion: With regard to the push-out bond strength of the fiber post to dentin, NaOCl and HEBP-NaOCl increased bond strength compared to other groups. NaOCl and HEBP-NaOCl have lower microhardness of dentin. Compared to HEBP, EDTA increases microhardness and does not make a significant difference in push-out bond strength. Therefore, it is recommended to use HEBP alone.

Amaç: Bu çalışmanın amacı, sodyum hipoklorit (NaOCl), klorheksidin [chlorhexidine (CHX)], etilen diamin tetra asetik asit (EDTA) ve etidronik asit (HEBP) solüsyonlarının fiber postların kök kanalına dentinine bağlanma mukavemeti ve kök dentin mikrosertliğine etkisini değerlendirmektir. Gereç ve Yöntemler: Altmış adet insan üst çene santral kesici dişi mine sement sınırının altından kesilerek, kökler endodontik olarak tedavi edildikten sonra irrigasyon protokolüne göre 6 gruba (n=10) ayrılmıştır: (1) Distile su, (2) CHX, (3) HEBP-NaOCl kombinasyonu, (4) HEBP, (5) %2,5 NaOCl, (6) %17 EDTA. Fiber postlar self-etch rezin siman ile dişlere simante edilmiştir ve örneklerden 1 mm kalınlığında kesitler alınarak, koronal üçlüdeki ilk kesit dentin mikrosertliği analizi için ve diğer kesitler push-out bağlanma gücü testi için kullanılmıştır. Veriler, Shapiro-Wilk, One-way ANOVA, Games-Howell testi kullanılarak istatistiksel olarak analiz edilmiştir. Bulgular: En düşük mikrosertlik HEBP-NaOCl ve NaOCl’de gözlenmiştir (p<0,05). CHX, HEBP ve EDTA, diğer gruplara kıyasla mikrosertlikte daha az azalma ile sonuçlanmıştır (p<0,05). Servikal bölgede HEBP-NaOCl ve NaOCl, diğer gruplara göre anlamlı derecede daha yüksek bağlanma kuvveti göstermiştir (p<0,05). Sonuçlar: Fiber postun dentine bağlanma kuvvetiyle ilgili olarak, NaOCl ve HEBP-NaOCl, diğer gruplara kıyasla bağlanma gücünü artırmıştır. Çalışmanın sonuçları değerlendirildiğinde, NaOCl ve HEBP-NaOCl, daha düşük dentin mikrosertliğine sahip olduğu görülmüştür. HEBP ile karşılaştırıldığında, EDTA kullanımı mikrosertliği artırmış ve push-out bağlanma gücünde önemli bir fark oluşturmamıştır. Bu nedenle HEBP’nin tek başına kullanılması tavsiye edilir.
Farklı irrigasyon solüsyonlarının fiber postların kök kanal dentinine bağlanma mukavemeti ve dentin mikrosertliği üzerindeki etkisi: Metadolojik çalışma
Keywords: Etidronic Acid; Root Canal Treatment; Sodium Hypochlorite; Etidronik Asit; Kök Kanal Tedavisi; Sodyum Hipoklorit